Yaroslav Prymachenko. Life of Vasyl’ Lyaskorons’ky - Primachenko, Yaroslav (Young Scholars Grinchenko – Seton International Journal, 2021)
Abstract. The article is devoted to the personality of Vasyl’ Lyaskoron’sky, the famous Ukrainian historian, scientist, public figure, archaeologist, numismatist, cartographer, writer, ethnographer, follower of Kyiv Historical School of Professor Antonovych in St. Volodymyr University. The relevance of the study consists in researching the life and activity of Vasyl’ Lyaskoron’sky. We are convinced that Vasyl’ Lyaskoronsky life, diverse activities and his contribution to the Ukrainian historical science and education require popularization and comprehensive study. Personally, I was very impressed by the fact that this noble, decent and a very modest man carried throughout his difficult life the beliefs and ideals that he adopted in his youth from the scientific supervisor Professor Antonovych. Vasyl’ Lyaskorons’ky remained devoted to the cause of Ukrainianness for the rest of his life. He became a prominent scientist and teacher. The life and activity of Vasyl’ Lyaskorons’ky can be considered a vivid example of a life devoted to Ukrainian science and education. Keywords: Vasyl’ Lyaskoron’sky, life and activity, Ukrainian historian, cartographer, archeologist, numismatist, writer, ethnographer, St. Volodymyr University, Kyiv Historical School of Professor Antonovych, second half of the 19th – first third of the 20th century, Kyiv.